Bordah Art as Local Wisdom in Coastal Malay Communities in Labuhan Batu Regency - Danny Ivanno Ritonga (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
The purpose of this study was to determine the local wisdom contained in the coastal Malay community in Labuhan Batu, North Sumatra. This research is also to find out changes in bordah art and understand the function of bordah art in coastal Malay communities in North Labuhanbatu. In discussing this study, Jacqueline Smith's theory of form was used which stated that it has a form, the form of the whole system, unity, characteristic or mode and Farley's theory of change which stated that social change is a change in behavior patterns, social relations, institutions and social structures at a certain time. Based on the results of the research conducted, it can be seen that the art of Bordah in Arabic is qasidah which contains poetry about worship, praise and prayers to the Prophet, namely Muhammad SAW. , where they recite prayers from books and sound drums as if they were singing songs like singing. Bordah art is also displayed in festivals, hagaf, birth celebrations and circumcision and marriage events. The function of music is as entertainment, accompaniment, means of communication, expression of gratitude, cultural continuity and means of self-expression. Keywords: Bordah, local wisdom, existence, function of music